Review Gray’s Anatomy: The Anatomical Basis of Clinical Practice / 41th edition. – Elsevier, 2015. – 1584 p. - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2015)
In 1858, Dr. Henry Gray and Henry Carter created a book for their fellow surgeons, which became a solid standard among anatomical works. After more than 150 years of continuous publication, Gray’s Anatomy remains the most comprehensive, comprehensive reference on this issue, offering access to the information necessary to provide safe, effective practice.